Magnetic target and magnetic target assembly
By optimizing the composition and distribution of oxides in magnetic material targets with Pt, Cr, Ru, and Ti, the issue of particle formation during sputter film formation is mitigated, improving the yield and quality of magnetic recording media.
Patent Information
- Application Number
- JP2024058166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The challenge in producing magnetic material targets for vertical magnetic recording in hard disk drives is the occurrence of oxide particles during sputter film formation, which leads to decreased yield due to arching and adherence to the substrate, particularly with increasing B oxide content.
The magnetic material targets are formulated with specific compositions of Pt, Cr, Ru, and Ti, along with controlled concentrations of B and O, and their oxides, ensuring fine distribution and minimized oversized oxide areas to suppress particle generation during sputter film formation.
The solution effectively reduces the occurrence of oxide particles during sputter film formation, enhancing the yield and quality of magnetic recording media by maintaining fine oxide distribution and preventing arching.
Smart Images

Figure 0007625113000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic material target and a magnetic material target assembly, and mainly to a magnetic material target for the production of a membrane for a HDD. [Background technology]
[0002] The layers constituting hard disk drives (HDDs) that employ perpendicular magnetic recording are made of materials based on ferromagnetic metals such as Co, Fe, and Ni, and the recording layers are often made of composite materials consisting of ferromagnetic alloys such as Co-Cr, Co-Pt, and Co-Cr-Pt, which are mainly composed of Co, and non-magnetic inorganic materials. Thin films for magnetic recording media such as hard disk drives are often produced by sputtering magnetic targets containing the above materials, due to their high productivity.
[0003] In general, magnetic material targets are manufactured by first crushing and mixing raw material powders, and then hot pressing the resulting mixture to obtain a sintered body. After this, in order to increase the density of the sintered body, HIP (Hot Isostatic Pressing) processing may be performed. The sintered body thus obtained is processed by a lathe to manufacture a target of a predetermined shape (Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6445126 [Patent Document 2] Patent No. 6332869 [Patent Document 3] Patent No. 6958819 Summary of the Invention [Problem to be solved by the invention]
[0005] As mentioned above, composite materials consisting of ferromagnetic alloys mainly composed of Co and non-magnetic inorganic materials are useful as recording layers for HDDs, and are sputter-deposited by HDD media manufacturers to form thin films with a granular structure in which magnetic particles are separated by oxide grain boundaries. In recent years, there has been a trend toward increasing the proportion of B oxides in the added oxides in perpendicular magnetic recording media that use Co as the main component of magnetic particles.
[0006] One of the problems in sputtering a magnetic material target containing oxides and mainly composed of Co is the generation of arcing from coarse oxides. If particles are generated from arcing and adhere to the substrate, the yield of the media decreases. For this reason, in the manufacture of a magnetic material target containing oxides and mainly composed of Co, it has been important to manufacture a target in which oxides are finely dispersed in the master alloy phase. On the other hand, the oxide of B is a low-melting material among the oxide species added in the manufacture of a magnetic material target containing oxides and mainly composed of Co, and the amount of B oxide added has been increasing in recent years. For this reason, it has become difficult to manufacture a target in which oxides are finely dispersed using conventional techniques, and particles are more likely to be generated during sputtering.
[0007] Therefore, an object of an embodiment of the present invention is to provide a magnetic material target and a magnetic material target assembly that contain oxides and that are mainly composed of Co, in which the generation of particles during sputtering film formation is effectively suppressed. [Means for solving the problem]
[0008] The above problems are solved by the present invention, which is specified as follows. (1) One or more of Pt, Cr, Ru, B, and Ti; An oxide, and the balance being Co and optionally containing impurities; The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more, The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The oxide comprises an oxide of B, Observation field area: 11569μm 2 per unit, 3.0μm 2 The number of the oxides having an area of more than 60 is 60 or less. (2) One or more of Pt, Cr, Ru, B, and Ti; An oxide, and the balance being Co and optionally containing impurities; The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more, The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The oxide comprises an oxide of B, Observation field area: 11569μm 2 per unit, 2.5μm 2 The number of the oxides having an area of more than 100 is 100 or less. (3) one or more of Pt, Cr, Ru, B, and Ti; An oxide, and the balance being Co and optionally containing impurities; The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more, The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The oxide comprises an oxide of B, Observation field area: 11569μm 2 per unit, 2.0μm 2 The number of the oxides having an area of more than 150 is 150 or less. (4) One or more of Pt, Cr, Ru, B, and Ti; An oxide, and the balance being Co and optionally containing impurities; The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more, The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, The oxide comprises an oxide of B, Observation field area: 11569μm 2 per 1.0μm 2 The number of the oxides having an area of more than 400 is 400 or less. (5) 1.0 μm 2 The number of oxides having an area of more than 0.5 μm 2 Ultra~1.0μm 2 The magnetic material target according to any one of (1) to (4), wherein a value obtained by dividing the area by the number of the oxides having the following area is 0.70 or less. (6) 0.5 μm 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm or less is determined. 2 6. The magnetic material target according to claim 1, wherein a value obtained by dividing the area by the number of the oxides having an area of more than 1.5 is 1.5 or more. (7) The magnetic material target according to any one of (1) to (6), wherein the oxide further contains one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr. (8) A magnetic material target according to any one of (1) to (7), a backing plate bonded to the magnetic material target; 1. A magnetic material target assembly comprising: Effect of the Invention
[0009] According to an embodiment of the present invention, it is possible to provide a magnetic material target and a magnetic material target assembly that contain oxides and that are mainly composed of Co, in which generation of particles during sputtering film formation is effectively suppressed. [Brief description of the drawings]
[0010] [Figure 1] This shows an example of a binarized image and the original image in image analysis using ImageJ. [Diagram 2]This is a screenshot of the settings for binarization processing using ImageJ. [Diagram 3] 1 is a SEM image of Example 1. [Figure 4] 1 is a SEM image of Example 2. [Diagram 5] 1 is a SEM image of Example 3. [Figure 6] 1 is an SEM image of Example 4. [Figure 7] 1 is an SEM image of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Next, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiments, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0012] <Magnetic material target> The shape of the magnetic material target according to the embodiment of the present invention is not particularly limited, and may be a flat plate (including a disk or rectangular plate), a cylindrical shape, or any other shape.
[0013] The magnetic material target according to the embodiment of the present invention contains at least one of Pt, Cr, Ru, and Ti, an oxide, and the balance is Co and selectively contained impurities. By using the magnetic material target according to the embodiment of the present invention as a sputtering target, a thin film for a magnetic recording medium such as a hard disk drive (HDD) can be produced.
[0014] In the magnetic material target according to the embodiment of the present invention, the total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more. When the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is 50 at% or more, the magnetic properties are improved. The upper limit of the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is not particularly limited, but is preferably 90 at% or less from the viewpoint of securing the grain boundary material. Moreover, the total concentration of Co, Pt, Cr, Ru, and Ti in the magnetic material target is more preferably 50 to 85 at%, and even more preferably 50 to 80 at%. Moreover, the concentration of Cr is preferably 10 at% or less, and more preferably 7 at% or less.
[0015] In the magnetic material target according to the embodiment of the present invention, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. With such a configuration, a particularly preferable magnetic thin film can be obtained. In the magnetic material target according to the embodiment of the present invention, the concentration of B is preferably 10 to 16 at%, and more preferably 11 to 15 at%. In the magnetic material target according to the embodiment of the present invention, the concentration of O is preferably 15 to 28 at%, and more preferably 16 to 26 at%.
[0016] The magnetic material target according to the embodiment of the present invention contains, as an oxide, an oxide of B. An example of the oxide of B is B2O3. Here, how to determine whether B is contained in the form of B2O3 in the magnetic material target according to the embodiment of the present invention will be described below. First, the magnetic material target is cut and the cross section is mirror-polished to obtain a sample for microstructure observation. More specifically, the cross section of the magnetic material target is polished in sequence using abrasive cloths and papers with grit sizes ranging from P80 to P2000, and finally buffed with aluminum oxide abrasive grains with a particle size of 0.3 μm to obtain a sample for microstructure observation having a cross-sectional polished surface. In addition, at this time, aluminum oxide and granular polishing debris attached to the polished surface are removed by washing. Next, element mapping is performed by performing WDX mapping analysis (Wave Length-dispersive X-ray Mapping Spectroscopy) in a field of view of 50 μm × 50 μm using FE-EPMA (Field Emission-Electron Probe Micro Analysis) on the sputtered surface of the sample after mirror polishing. The WDX mapping analysis in a field of view of 50 μm × 50 μm using FE-EPMA was performed at an acceleration voltage of 15.0 kV and an irradiation current of 2.0 × 10 -8 This can be done by performing a stage scan under the condition of A. At this time, if the areas where the detection intensity of B and O are high coincide with each other, it is considered that the B is mostly present in the sintered body as an oxide. Therefore, B where the area where the detection intensity is high coincides with O is judged to be present in the form of B2O3. In addition to B2O3, the oxide may further contain one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr in order to further improve the magnetic properties.
[0017] In the magnetic material target according to the embodiment of the present invention, the volume fraction of oxide is 30 vol.% or more. When the volume fraction of oxide in the magnetic material target is 30 vol.% or more, the magnetic properties are further improved. There is no particular upper limit to the volume fraction of oxide in the magnetic material target, but from the viewpoint that the magnetic properties deteriorate when there is too much oxide, it is preferably 60 vol.% or less. Moreover, the volume fraction of oxide in the magnetic material target is more preferably 30 to 55 vol.%, and even more preferably 30 to 50 vol.%. The volume fraction of oxide can be calculated from the composition of the target, and the volume of each component contained in the target is calculated by (content of each material: mol) × (molecular weight of each material: g / mol) × (reciprocal of density of each material: cm 3 Next, the volume fraction of oxides can be calculated by dividing the total volume of only oxides among the components by the total volume of all components.
[0018] The remainder of the magnetic material target according to the embodiment of the present invention may or may not contain impurities. Examples of the impurities include metal elements such as Fe, Ni, Cu, Zr, Al, W, V, Zn, Cu, Zn, Sn, and Ta, and elements such as C or N from gas components such as carbon dioxide and nitrogen in the atmosphere, or compounds thereof. The content of the impurities contained in the remainder of the magnetic material target according to the embodiment of the present invention may be 0.5 mol% or less, or may be 0.15 mol% or less. In addition, the impurities can be analyzed by taking an analysis sample from the magnetic material target and using infrared absorption spectrometry, an ICP optical emission spectrometer, GDMS (glow discharge mass spectrometry), or the like. The amount and shape of the analysis sample vary depending on the analysis method used, and the optimal amount and shape for each method can be selected.
[0019] The magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 per unit, 3.0μm 2In the magnetic material target according to the embodiment of the present invention, as described above, the oxide contains an oxide of B, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. In general, the higher the oxygen concentration, the higher the possibility of containing coarse oxides, which makes it easier for arcing to occur during sputtering film formation, resulting in the problem of particles being generated. In contrast, the magnetic material target according to the embodiment of the present invention has an O concentration of 13.5 at% or more, yet has an observation field area of 11569 μm 2 per unit, 3.0μm 2 The number of oxides with an area of more than 1000 mm is controlled to 60 or less. This ensures that the oxide structure is sufficiently fine, effectively suppressing the occurrence of arcing during sputtering film formation. Since oxides have a slower sputtering rate than metals, it is believed that protruding oxides remain when sputtering discharge is carried out for a long period of time. It is believed that arcing occurs due to electric field concentration on these protrusions. Here, if the oxide structure is sufficiently fine, the remaining protrusions will be small, making electric field concentration less likely to occur and arcing less likely to occur. Observation field area: 11,569 μm 2 per unit, 3.0μm 2 The number of oxides having an area of more than 11569 μm is preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, and even more preferably 20 or less. 2 per unit, 3.0μm 2 The lower limit of the number of oxides having an area of more than 100 nm is not particularly limited, but may be 0 or more, 1 or more, or 3 or more.
[0020] In another aspect, the magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 per unit, 2.5μm 2In the magnetic material target according to the embodiment of the present invention, as described above, the oxide contains an oxide of B, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. In general, the higher the oxygen concentration, the higher the possibility of containing coarse oxides, which makes it easier for arcing to occur during sputtering film formation, resulting in the problem of particles being generated. In contrast, the magnetic material target according to the embodiment of the present invention has an O concentration of 13.5 at% or more, yet has an observation field area of 11569 μm 2 per unit, 2.5μm 2 The number of oxides with an area of more than 100 is controlled to 100 or less. As a result, the oxide structure is sufficiently fine, and the occurrence of arcing during sputtering film formation is effectively suppressed. Since the sputtering rate of oxides is slower than that of metals, it is believed that if sputtering discharge is carried out for a long period of time, the oxides will remain in the form of protrusions. It is believed that arcing occurs due to electric field concentration on these protrusions. Here, if the oxide structure is sufficiently fine, the remaining protrusions will be small, making electric field concentration less likely to occur and arcing less likely to occur. Observation field area: 11,569 μm 2 per unit, 2.5μm 2 The number of oxides having an area of more than 11569 μm is preferably 75 or less, more preferably 55 or less, even more preferably 45 or less, and even more preferably 25 or less. 2 per unit, 2.5μm 2 The lower limit of the number of oxides having an area of more than 100 nm is not particularly limited, but may be 0 or more, 1 or more, 2 or more, or 4 or more.
[0021] In yet another aspect, the magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 per unit, 2.0μm 2In the magnetic material target according to the embodiment of the present invention, as described above, the oxide contains an oxide of B, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. In general, the higher the oxygen concentration, the higher the possibility of containing coarse oxides, which makes it easier for arcing to occur during sputtering film formation, resulting in the problem of particles being generated. In contrast, the magnetic material target according to the embodiment of the present invention has an O concentration of 13.5 at% or more, yet has an observation field area of 11569 μm 2 per unit, 2.0μm 2 The number of oxides with an area of more than 100 is controlled to 150 or less. As a result, the oxide structure is sufficiently fine, and the occurrence of arcing during sputtering film formation is effectively suppressed. Since the sputtering rate of oxides is slower than that of metals, it is believed that if sputtering discharge is carried out for a long period of time, the oxides will remain in the form of protrusions. It is believed that arcing occurs due to electric field concentration on these protrusions. Here, if the oxide structure is sufficiently fine, the remaining protrusions will be small, making electric field concentration less likely to occur and arcing less likely to occur. Observation field area: 11,569 μm 2 per unit, 2.0μm 2 The number of oxides having an area of more than 100 is preferably 100 or less, more preferably 80 or less, even more preferably 50 or less, and even more preferably 30 or less. 2 per unit, 2.0μm 2 The lower limit of the number of oxides having an area of more than 100 nm is not particularly limited, but may be 0 or more, 1 or more, 2 or more, 3 or more, or 5 or more.
[0022] In yet another aspect, the magnetic material target according to the embodiment of the present invention has an observation field area of 11569 μm 2 per 1.0μm 2In the magnetic material target according to the embodiment of the present invention, as described above, the oxide contains an oxide of B, the concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more. In general, when the oxygen concentration is high, there is a high possibility that coarse oxides will be contained, in which case arcing is likely to occur during sputtering film formation, resulting in the problem of particles being generated. In contrast, the magnetic material target according to the embodiment of the present invention has an O concentration of 13.5 at% or more, yet has an observation field area of 11569 μm 2 per 1.0μm 2 The number of oxides with an area of more than 1000 is controlled to 400 or less. As a result, the oxide structure is sufficiently fine, and the occurrence of arcing during sputtering film formation is effectively suppressed. Since the sputtering rate of oxides is slower than that of metals, it is believed that if sputtering discharge is carried out for a long period of time, the oxides will remain in the form of protrusions. It is believed that arcing occurs due to electric field concentration on these protrusions. Here, if the oxide structure is sufficiently fine, the remaining protrusions will be small, making electric field concentration less likely to occur and arcing less likely to occur. Observation field area: 11,569 μm 2 per 1.0μm 2 The number of oxides having an area of more than 11569 μm is preferably 300 or less, more preferably 200 or less, and even more preferably 150 or less. 2 per 1.0μm 2 The lower limit of the number of oxides having an area of more than 100 nm is not particularly limited, but may be 20 or more, or may be 50 or more.
[0023] The magnetic material target according to the embodiment of the present invention has a thickness of 1.0 μm. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 It is preferable that the value obtained by dividing the area by the number of oxides having an area of 1.0 μm or less is 0.70 or less. 2 The number of oxides with a large area of over 0.5 μm 2 Ultra~1.0μm2 Since the number of oxides having a small area of 1.0 μm or less is present at a ratio of 0.70 or less, the structure of the oxides is sufficiently fine, and the occurrence of arcing during sputtering deposition is effectively suppressed. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The value divided by the number of oxides having an area of 1.0 μm or less is more preferably 0.6 or less, even more preferably 0.4 or less, even more preferably 0.3 or less, and even more preferably 0.2 or less. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The lower limit of the value divided by the number of oxides having the area below is not particularly limited, but may be 0.0 or more, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, or 0.1 or more.
[0024] The magnetic material target according to the embodiment of the present invention has a thickness of 0.5 μm. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 It is preferable that the value obtained by dividing the number of oxides having an area of more than 0.5 μm by the number of oxides having an area of more than 0.5 μm is 1.5 or more. 2 Ultra~1.0μm 2 The number of oxides with an area of 1.0 μm or less 2 Since the ratio of the oxide particles having a large area of more than 0.5 μm is 1.5 or more, the oxide structure is sufficiently fine, and the occurrence of arcing during sputtering deposition is effectively suppressed. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2The value divided by the number of oxides having an area of more than 0.5 μm is more preferably 1.5 or more, even more preferably 2.5 or more, even more preferably 3.5 or more, and even more preferably 4.5 or more. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 The upper limit of the value divided by the number of oxides having an area of more than 1000 mm is not particularly limited, but may be 8.0 or less, or may be 6.0 or less.
[0025] The observation field area of the magnetic material target according to the embodiment of the present invention is 11569 μm 2 per unit, 3.0μm 2 Oxide with an area of more than 2.5μm 2 Oxide with an area of more than 2.0μm 2 Oxides with an area of more than 1.0 μm 2 Number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The method for measuring the number of oxide particles having the following areas is described in detail below. First, the magnetic material target is cut and the cross section is mirror-polished to obtain a sample for microstructural observation. More specifically, in the mirror-polishing, the cross section of the magnetic material target is polished in order using abrasive cloths and papers with grit sizes ranging from P80 to P2000, and finally buffed using aluminum oxide abrasive grains with a particle size of 0.3 μm to obtain a sample for microstructural observation having a polished cross section. In addition, at this time, the aluminum oxide and granular polishing debris adhering to the polished surface are thoroughly removed by washing. Next, a secondary electron image of the mirror-polished sputtered surface of the sample is taken using an FE-SEM (product name: SU3900, manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 15 kV and a magnification of 1000. In the secondary electron image, the metal matrix phase appears as a brighter area than the surrounding area, and the oxide appears as a darker area than the surrounding area. Next, the SEM image (field of view area 11569 μm 2) is binarized by the mode method using image processing software (ImageJ manufactured by the National Institutes of Health), and the area of each oxide is measured using the AnalyzeParticles function of the image processing software. Particles (oxides) in the field of view are extracted, and the area of each particle is calculated. 2 Oxide with an area of more than 2.5μm 2 Oxide with an area of more than 2.0μm 2 Oxides with an area of more than 1.0 μm 2 Oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The number of oxides having the following areas is counted: The binarization using ImageJ is carried out according to the steps (1) to (5) below. (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 1000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. As described above, the areas that are darker than the surrounding areas that are classified as black by the binarization process are converted to black, and the black areas are considered to be oxides. The threshold for the binarization process is automatically set from the color histogram in the image. Figure 1 shows an example of an image binarized by ImageJ and the original image.
[0026] <Magnetic target assembly> The magnetic material target according to the embodiment of the present invention may be bonded to a backing plate as necessary to form a magnetic material target assembly. The magnetic material target assembly may be mounted on a sputtering device and used. As the brazing material, indium or indium tin may be used. The magnetic material target according to the embodiment of the present invention may be mounted on a sputtering device as it is without using a backing plate. The material of the backing plate is not particularly limited, and examples thereof include Cu, Ti, Mo, and alloys containing at least one of these (e.g., Cu-Ni-Si alloys (e.g., C18000, etc.), CuZn alloys, and CuCr alloys). The material of the backing plate preferably has a high thermal conductivity, and from this viewpoint, Cu is suitable.
[0027] <Method of manufacturing magnetic material target> Hereinafter, a method for manufacturing a magnetic material target according to an embodiment of the present invention will be described in detail. The magnetic material target according to the embodiment of the present invention can be manufactured by a powder sintering method. First, powders of each metal element are prepared. Also, instead of the powders of each metal element, alloy powders of these metals (for example, Co-Pt powder) may be used. In particular, it is preferable to use Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder. Note that using B2O3 powder as a raw material is not preferable because the obtained magnetic material target may contain coarse oxides. Regarding the 50% cumulative volume grain size D50 (average grain size D50) of each raw material powder, the following sizes can be used: Co powder: 1 to 10 μm, CrBO3 powder: 0.5 to 5 μm, Pt powder: 1 to 10 μm, Co2B2O5 powder: 1 to 20 μm, and Co2B powder: 1 to 50 μm. The purity of these raw materials is usually 2N (99 mass%) or more, preferably 3N (99.9 mass%) or more, and more preferably 4N (99.99 mass%) or more. If the purity is lower than 2N, the sintered body will contain a large amount of impurities, which may cause problems such as the failure to obtain the desired physical properties (for example, generation of particles due to arcing). These raw materials can be appropriately prepared based on the composition and purity of the desired sintered body.
[0028] These metal powders are then weighed out to obtain the desired composition, and mixed using a mixer that also serves as a grinder. Non-magnetic particles may also be mixed with the metal powder at this stage. As a mixer, a ball mill, a mortar, or the like may be used, but it is preferable to use a powerful mixing method such as a ball mill. In addition, in consideration of the problem of oxidation during mixing, it is preferable to mix in an inert gas atmosphere or in a vacuum.
[0029] Here, the mixing is performed by carrying out primary mixing, followed by sieving, and then secondary mixing. The primary mixing is carried out for 5 to 30 hours. The secondary mixing is carried out for 5 to 30 hours. By extending the mixing time of the raw materials, the observation field area is 11569 μm 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides having an area of more than 1.0 μm can be reduced. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The area divided by the number of oxides having an area of less than 0.5 μm can be reduced. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 On the other hand, by shortening the mixing time of the raw materials, the observation field area of 11569 μm 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides having an area of more than 1.0 μm can be increased. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2The area divided by the number of oxides having an area of less than 0.5 μm can be increased. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 It is possible to reduce the value obtained by dividing the number of oxides having an area of more than 11569 μm by the number of oxides having an area of more than 11569 μm. Also, by performing sieving between the primary mixing and the secondary mixing, it is possible to remove coarse powder and increase the amount of fine powder in the secondary mixing. As a result, it is possible to suppress the coarsening of the oxides. The sieving is performed using a sieve with an opening size of 150 to 400 μm. From this perspective, it is possible to reduce the observation field area of 11569 μm by adjusting the mixing time of the raw materials. 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 Divided by the number of oxides with an area of less than 0.5 μm 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 The value divided by the number of oxides having an area of more than 1000 nm can be controlled.
[0030] The mixed powder thus obtained is molded and sintered using a hot press device to produce a sintered body. The molding and sintering is not limited to hot pressing, and plasma discharge sintering and hot isostatic sintering can also be used. The sintering conditions are 650-1400°C and 0.5-12 hours. By increasing the sintering temperature and / or the sintering time, the observation field area can be increased to 11569μm. 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 The number of oxides with an area of more than 1.0 μm 2The number of oxides having an area of more than 1.0 μm can be increased. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The area divided by the number of oxides having an area of less than 0.5 μm can be increased. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 On the other hand, if the sintering temperature is lowered and / or the sintering time is shortened, the observation field area of 11569 μm2 can be reduced. 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides having an area of more than 1.0 μm can be reduced. 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The area divided by the number of oxides having an area of less than 0.5 μm can be reduced. 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 From this viewpoint, the value obtained by dividing the number of oxides having an area of 11569 μm by the number of oxides having an area of 11569 μm can be increased by adjusting the sintering temperature and sintering time. 2 per unit, 3.0μm 2 Number of oxides with an area of more than 2.5 μm 2 Number of oxides with an area of more than 2.0 μm 2 Number of oxides with an area of more than 1.0 μm 2 The number of oxides with an area of more than 1.0 μm 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 Divided by the number of oxides with an area of less than 0.5 μm 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm2 The value divided by the number of oxides having an area of more than 1000 nm can be controlled.
[0031] The sintered body is then removed from the hot press and subjected to HIP (Hot Isostatic Pressing). HIP is an effective means for increasing the density of the sintered body. The holding temperature during HIP is 650-1100°C, the holding time is 0.5-12 hours, and the pressure is 100 MPa or more. The sintered body thus obtained is then machined on a lathe into a desired shape to produce a magnetic material target.
[0032] <Film formation method using a magnetic material target> Using the magnetic material target according to the embodiment of the present invention, a thin film that mainly constitutes a magnetic recording medium can be formed. Specifically, a sputtering device is used to sputter the surface of the magnetic material target with accelerated argon ions, particles (sputtered particles) are released from the magnetic material target, and the sputtered particles are deposited on the surface of a substrate that is placed in a position opposite to the target, thereby forming a thin film on the surface of the substrate. The sputtering conditions can be appropriately set depending on the desired film thickness, composition, etc. EXAMPLES
[0033] The following examples of the present invention are provided for a better understanding of the present invention and its advantages, and are not intended to limit the invention.
[0034] <Example 1> The magnetic material target according to Example 1 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0035] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, the magnetic material target according to Example 1 was produced.
[0036] <Example 2> The magnetic material target according to Example 2 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 30μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0037] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 2 was produced.
[0038] <Example 3> The magnetic material target according to Example 3 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 8 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 8 hours was performed in that order.
[0039] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2.5 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 3 was produced.
[0040] <Example 4> The magnetic material target according to Example 4 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, Co2B2O5 powder: 8μm, Co2B powder: 3μm Next, the weighed Co powder, CrBO3 powder, Pt powder, Co2B2O5 powder, and Co2B powder were placed in a ball mill pot together with zirconia balls, and primary mixing was performed for 10 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 10 hours was performed in that order.
[0041] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 750°C, and a holding time (sintering time) of 3 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding was completed, the material was allowed to cool naturally in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding was completed, the material was allowed to cool naturally in the furnace. In this way, a magnetic material target according to Example 4 was produced.
[0042] <Comparative Example 1> A magnetic material target according to Comparative Example 1 was manufactured by the following manufacturing method. As raw material powders, 3N (99.9 mass%) Co powder, CrBO3 powder, Pt powder, and B2O3 powder were prepared and weighed to have a composition of Co-Pt-Cr-BO (Pt 10-20 at%, Cr 0.5-7 at%, B 11-15 at%, O 16-26 at%, Co (balance)). The raw material powders were prepared so that the total composition was 100 at%. The 50% cumulative volume particle size D50 (average particle size D50) of the raw material powders was as follows: Co powder: 4μm, CrBO3 powder: 1μm, Pt powder: 3μm, B2O3 powder: 10μm Next, the weighed Co powder, CrBO3 powder, Pt powder, and B2O3 powder were placed in a ball mill pot together with zirconia balls, and the mixture was subjected to primary mixing for 12 hours, sieving through a sieve with 150 μm openings, and secondary mixing for 5 hours, in that order.
[0043] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 800°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was naturally cooled in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 750°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was naturally cooled in the furnace. In this way, a magnetic material target according to Comparative Example 1 was produced.
[0044] Observation field area: 11569μm 2 Evaluation of the number of oxides having a given area per Each of the magnetic material targets of Examples 1 to 4 and Comparative Example 1 was cut and the cross section was mirror-polished to obtain a sample for observing the structure. Next, secondary electron images of the sputtered surface of the mirror-polished sample were taken using an FE-SEM (product name: SU3900, manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 15 kV and a magnification of 1000. The taken SEM images are shown in Figure 3 (Example 1), Figure 4 (Example 2), Figure 5 (Example 3), Figure 6 (Example 4), and Figure 7 (Comparative Example 1), respectively. Next, the SEM image (field of view area 11569 μm 2 ) was binarized by the mode method using image processing software (ImageJ manufactured by the National Institutes of Health), and the area of each oxide was measured using the AnalyzeParticles function of the image processing software. Grains (oxides) in the field of view were extracted, and the area of each grain was calculated. 2 Oxide with an area of more than 2.5μm 2 Oxide with an area of more than 2.0μm 2 Oxides with an area of more than 1.0 μm 2 Oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2The number of oxide particles having the following areas was counted: The above ImageJ binarization was carried out according to the steps (1) to (5) below. (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 1000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. A screenshot of the setting conditions is shown in Figure 2. As described above, after importing the SEM image with ImageJ, a binarization process was performed to convert the areas on the SEM image that were darker than the surrounding areas that were classified as black by the binarization process into black, and the black areas were considered to be oxides. The area of the black areas was calculated and the area was reduced to 3.0 μm 2 Oxide with an area of more than 2.5μm 2 Oxide with an area of more than 2.0μm 2 Oxides with an area of more than 1.0 μm 2 Oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 The number of oxide particles having the following areas was counted: Based on the above measurement results, 1.0 μm 2 The number of oxides with an area of more than 0.5 μm 2 Ultra~1.0μm 2 Divided by the number of oxides having an area of 0.5 μm 2 Ultra~1.0μm 2 The number of oxides having an area of 1.0 μm 2 The values were calculated by dividing the area by the number of oxides having an area of more than 100 nm.
[0045] A magnetic material target was manufactured by a composition and manufacturing method similar to those of Examples 1 to 4, and a WDX mapping analysis was performed in a field of view of 50 μm × 50 μm by FE-EPMA. The areas where the detection intensity of B and O was high were consistent. Therefore, it is considered that the magnetic material target contains an oxide of B. Therefore, it is expected that the magnetic material targets of Examples 1 to 4, which are examples of targets manufactured by a composition and manufacturing method similar to those of the test example, also contain an oxide of B. In addition, since the raw material powder in Comparative Example 1 contains B2O3 powder, it is expected that the magnetic material target of Comparative Example 1 also contains an oxide of B.
[0046] Particle evaluation The particle evaluation was carried out as follows. First, the magnetic material targets according to Examples 1 to 4 and Comparative Example 1 were cut by a lathe to a shape of 165.1 mm in diameter and 4.0 mm in thickness to prepare disk-shaped targets. These were attached to a magnetron sputtering device (C-3010 sputtering system manufactured by Canon Anelva Corporation) and sputtering was performed. The sputtering conditions were an input power of 1 kW and an Ar gas pressure of 1.7 Pa. After performing pre-sputtering at 1 kWhr, a film was formed on a 4-inch silicon substrate for 20 seconds. Next, for each of Examples 1 to 4, the number of particles with a particle size of 0.09 μm or more that adhered to the substrate was measured using a particle counter. A Candela CS920 (manufactured by KLA Tencor Corporation) was used as the particle counter. A laser was irradiated onto the wafer on which a film was formed by sputtering, and the particles were identified by detecting the reflection and scattering of the laser.
[0047] [Table 1]
[0048] <Consideration> According to Table 1, the magnetic material targets according to Examples 1 to 4 each contain Pt, Cr, B, and an oxide, with the balance being Co, the total concentration of Co, Pt, and Cr is 50 at% or more, the concentration of B is 9 at% or more, the concentration of O is 13.5 at% or more, an oxide of B is contained, and the field area is 11569 μm 2 per unit, 3.0μm 2 The number of oxides with an area of more than 2.5 μm is 60 or less. 2 The number of oxides with an area of more than 2.0 μm is 100 or less. 2 The number of oxides with an area of more than 1.0 μm is 150 or less, or 2 The number of oxides having an area of more than 400 was less than 400. Therefore, the generation of particles during the sputtering film formation was effectively suppressed. In contrast, the magnetic material target according to Comparative Example 1 had a field area of 11569 μm 2 per unit, 3.0μm 2 More than 60 oxides with an area of 2.5 μm or more 2 The number of oxides with an area of more than 2.0 μm is more than 100. 2 The number of oxides with an area of more than 1.0 μm is more than 150, or 2 The number of oxide particles each having an area of more than 400 was more than 400. For this reason, the generation of particles during the sputtering film formation could not be suppressed.
[0049] According to one embodiment of the present invention, a magnetic material target and a magnetic material target assembly containing oxides and mainly composed of Co, in which particle generation during sputtering film formation is well suppressed, can be obtained, which may contribute to the sophistication of thin film formation technology by sputtering used in the manufacture of magnetic recording hard disk media, etc. Therefore, one embodiment of the present invention may contribute to Goal 9 of the Sustainable Development Goals (SDGs) led by the United Nations, "Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation."
Claims
1. One or more of Pt, Cr, Ru, B, and Ti; An oxide of B; with the balance being Co and optionally containing impurities; Co is the main component, The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more; The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, Observation field area: 11569 μm 2 per 3.0 μm 2 The number of the oxides having an area of more than 60 is 60 or less.
2. One or more of Pt, Cr, Ru, B, and Ti; An oxide of B; with the balance being Co and optionally containing impurities; Co is the main component, The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more; The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, Observation field area: 11569 μm 2 per 2.5 μm 2 The number of the oxides having an area of more than 100 is 100 or less.
3. One or more of Pt, Cr, Ru, B, and Ti; An oxide of B; with the balance being Co and optionally containing impurities; Co is the main component, The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more; The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, Observation field area: 11569 μm 2 per 2.0 μm 2 The number of the oxides having an area of more than 150 is 150 or less.
4. One or more of Pt, Cr, Ru, B, and Ti; An oxide of B; with the balance being Co and optionally containing impurities; Co is the main component, The total concentration of Co, Pt, Cr, Ru, and Ti is 50 at% or more; The concentration of B is 9 at% or more, and the concentration of O is 13.5 at% or more, Observation field area: 11569 μm 2 per 1.0 μm 2 The number of the oxides having an area of more than 400 is 400 or less.
5. 1.0 μm 2 The number of the oxides having an area of more than 0.5 μm 2 Super ~1.0μm 2 The magnetic material target according to any one of claims 1 to 4, wherein a value obtained by dividing the area by the number of the oxides having the following area is 0.70 or less.
6. 0.5 μm 2 Super ~1.0μm 2 The number of oxides having an area of 1.0 μm or less is 2 The magnetic material target according to any one of claims 1 to 4, wherein a value obtained by dividing the area by the number of the oxides having an area of more than 1.5 is 1.5 or more.
7. A magnetic material target according to any one of claims 1 to 4, further containing one or more oxides of elements selected from Al, Si, Ba, Be, Ca, Ce, Cr, Co, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr.
8. The magnetic material target according to any one of claims 1 to 4, a backing plate bonded to the magnetic material target; 1. A magnetic material target assembly comprising:
Citation Information
Patent Citations
Origanic electrolyte cell
JP1988032869A
Manufacture of gaas compound semiconductor substrate
JP1989045126A
Target, method for manufacturing target, and method for manufacturing magnetic recording medium
JP2012033247A
Perpendicular magnetic recording medium, method of producing perpendicular magnetic recording medium, and perpendicular recording and reproducing device
JP2015153447A
Sputtering targets for magnetic recording media
JP6958819B2